Multiparametric 18F-Choline PET/MR in childhood and teenage-young adult gliomas: assessment of suspected disease progression. (12th October 2019) - Ferrazzoli, Valentina; Shankar, Ananth; V Cockle, Julia; Tang, Christine; Bomanji Francesco Fraioli, Jamshed; Hyare, Harpreet
Abstract: Aim: Evaluation of post-treatment glioma burden remains a significant challenge in childhood, Teenage and Young Adults (TYA). Although amino acid PET impacts on glioma imaging, 18 fluoro-Choline Positron Emission Tomography (ChoPET) is more widely available. The aim was to evaluate the utility of ChoPET/MRI for suspected disease progression in childhood and TYA gliomas. Methods: 27 consecutive patients with suspected glioma disease progression were evaluated with ChoPET/MR and 59 scans included. Relative cerebral blood volume (rCBV), ADC and SUVmax in enhancing (enh), non-enhancing (ne) tumour volumes and normal appearing white matter (wm) were calculated (rCBVenh, rCBVne, rCBVwm, ADCenh, ADCne, ADCwm, SUVenh, SUVne, SUVwm). Blinded nuclear medicine and neuroradiologist scored the images on tumour probability (1:unlikely-5:definitely). Receiver Operating Characteristic (ROC) analysis considering as gold standard histopathology or clinical follow-up was performed. Results: Combined ChoPET/MR accuracy was 100% for residual tumour, conventional MR accuracy was 96.3% (91.7% <14years, 100% ≥15years) and ChoPET accuracy was 73.1% (66.7% <14years, 80.0% ≥15 years). Lack ack of agreement in 9/27 with ChoPET superior to MR in 1 case. Tumour component analysis demonstrated significantly higher SUVenh and SUVne than SUVwm (SUVenh: p<0.001, SUVne: p=0.003) equivalent to ADC (ADCenh, ADCnenh: p<0.001) and rCBV (rCBVenh, rCBVnenh: p<0, 001). Conclusions: Combined ChoPET/MR has 100% accuracy in TYA gliomas with suspected disease progression. ChoPET is able to detect enhancing and non-enhancing tumour but it is more reliable for evaluating enhancing disease >15 years. In selected cases where MRI is equivocal, a quantitative multi-modality ChoPET/MR better defines both enhancing and non-enhancing tumour for improved assessment of childhood and TYA gliomas.